2015
DOI: 10.1039/c5cp02900g
|View full text |Cite
|
Sign up to set email alerts
|

From crystal to glass-like thermal conductivity in crystalline minerals

Abstract: The ability of some materials with a perfectly ordered crystal structure to mimic the heat conduction of amorphous solids is a remarkable physical property that finds applications in numerous areas of materials science, for example, in the search for more efficient thermoelectric materials that enable to directly convert heat into electricity. Here, we unveil the mechanism in which glass-like thermal conductivity emerges in tetrahedrites, a family of natural minerals extensively studied in geology and, more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 43 publications
(62 reference statements)
8
84
0
Order By: Relevance
“…8 As discussed previously, experimental INS data showed that the low energy modes (∼4 meV) shifted to lower energies with the decrease of temperatures, i.e., phonon softening upon cooling, for both Cu 10 Zn 2 Sb 4 S 13 and Cu 10 Zn 2 Sb 2 Te 2 S 13 tetrahedrites. 9 A similar feature was also observed in Cu 10.5 NiZn 0.5 Sb 4 S 13 (data not shown). To understand the nature of this softening, we investigated the temperature dependence of the low energy modes in Cu 10.5 NiZn 0.5 Sb 4 S 13 by looking into the FPMD trajectories.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…8 As discussed previously, experimental INS data showed that the low energy modes (∼4 meV) shifted to lower energies with the decrease of temperatures, i.e., phonon softening upon cooling, for both Cu 10 Zn 2 Sb 4 S 13 and Cu 10 Zn 2 Sb 2 Te 2 S 13 tetrahedrites. 9 A similar feature was also observed in Cu 10.5 NiZn 0.5 Sb 4 S 13 (data not shown). To understand the nature of this softening, we investigated the temperature dependence of the low energy modes in Cu 10.5 NiZn 0.5 Sb 4 S 13 by looking into the FPMD trajectories.…”
supporting
confidence: 64%
“…8 Another type of anomalous behavior is the phonon softening upon cooling, or stiffening upon heating, revealed by inelastic neutron scattering (INS) experiments, in which the decrease of low-energy vibration mode energies with the decrease of temperatures was observed. 9 While it was argued that this anomaly is also related to the dynamics of Cu12e, the detailed atomic mechanism remains elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…38 In Cu 12 Sb 2 Te 2 S 13 , the characteristic energy for the out-of-plane vibration mode of Cu(2) increased from 2.5 to 4.0 meV on heating from 2 K to 200 K, indicating the strong anharmonicity of the mode. 67 The low-energy weakly dispersive optical branch being coupled with acoustic phonons has been considered as the cause of low κ L of the tetrahedrite.…”
Section: Tetrahedrite (P-type)mentioning
confidence: 99%
“…The large and anisotropic thermal displacement parameters of the Cu2 atoms had been thought to play a major role in disrupting eiciently the heat-carrying acoustic waves. A detailed study of the latice dynamics of tetrahedrites has been undertaken recently using a combination of inelastic neutron scatering on poly-and single-crystalline tetrahedrites [46]. The conventional temperature dependence of the latice thermal conductivity in the Cu-deicient tetrahedrite Cu 10 Te 4 S 13 ofered an interesting experimental platform to unveil the microscopic mechanisms responsible for the low, glass-like thermal conductivity of tetrahedrites (Figure 7).…”
Section: Thermal Propertiesmentioning
confidence: 99%